Pengelolaan Lingkungan Pada Program Shrimp Estate Guna Pemenuhan Hak Atas Lingkungan Yang Baik dan Sehat - Aditya Khrisna Murti; Shafa Ataina Aurellia (Fakultas Hukum Universitas Islam Indonesia, 2024)
Shrimp ponds are one of the contributors to river and sea environmental pollution, therefore one of the programs of the Ministry of Maritime Affairs and Fisheries with the Shrimp Estate Project is that if it is not managed with good management it will cause degradation of the river and sea environment. The aim of this research is to assess the extent of the impact of shrimp ponds on river and marine ecosystems. Apart from that, it is also to look at the concept of protecting and managing shrimp estates in order to fulfill the right to a good and healthy environment. This type of research is juridical-normative using literature studies from various sources of statutory regulations, national journals. From the existence of shrimp estates, from land clearing, waste and harvesting which are not managed with good management, it can cause damage to river and sea ecosystems which impact mangrove land, decreasing water quality. The results of this literature study highlight the importance of considering many aspects of a shrimp estate.